Estetika Tari Betangas pada Sanggar Sultan Nata di Kabupaten Sintang Provinsi Kalimantan Barat - Fauziah, Rizka; Widyastutieningrum, Sri Rochana; Dewi, Maharani Luthvinda (Gesture: Jurnal Seni Tari, 2025)
The purpose of this study was to analyze the aesthetic value of Betangas dance at Sanggar Sultan Nata in Sintang Regency. Betangas dance is a new creative dance created by Musliyadi in 2014. Betangas dance uses basic Malay dance movements. This study is a qualitative study with an ethnochoreology approach and descriptive analysis method. Data collection techniques: observation, interviews, and literature studies. The aesthetic value in Betangas dance can be seen in the elements of movement, dance music, floor patterns, costume makeup and properties. The dance movements are inspired by the movements during the Betangas ceremony, the music uses Malay music, uses corrective makeup and costumes based on the Sintang Malay traditional dress, the properties used are woven pandan leaf mats and sarongs or tapeh. The aesthetics of Betangas dance are related to the life value of the Malay community, especially in Sintang Regency.